Sustainable cities: the relationships between urban built forms and density indicators - Ahmadian, Ehsan; Sodagar, Behzad; Mills, Glen; Byrd, Hugh; Bingham, Chris M.; Zolotas, Argyrios (Elsevier, 2020)
The paper introduces a novel indicator of urban built form termed Form Signature. Generic models of four urban built forms are developed including pavilion, terrace, court and a newly introduced tunnel-court which are used to compare and contrast their land-use performance and density characteristics. Selecting plot ratio and site coverage as the most popular and appropriate density indicators, the simultaneous relationship to each of the considered urban built forms is shown graphically with the number of storeys, plan depth and cut-off angle as the main variables of interest. For existing urban areas, the resulting graphs provide a robust tool for statistical analysis of contexts such as climate, economy, energy and crime potential and establish their relationship to form and density. To show the value of the contribution, analysing 32 case studies from 19 cities in different global locations showed an insignificant relationship between climate and form/density of urban areas, while practically depicting that urban areas built in court form acquire higher cut-off angle compared to terrace form urban developments. For the planning of future urban areas, the resulting relationships provide an application-oriented urban planning tool to facilitate the most effective land-use method in order to achieve sustainable cities. Examples showing the potential of the tool for future statistical energy and social analysis of urban areas are provided. Finally, a relative comparison shows that the newly-introduced tunnel-court form achieves the greatest density while pavilion achieves the lowest
Keywords: Sustainable cities; Urban planning; Land-use; Density indicators; Urban built form